KEBERADAAN ALAT MUSIK TRADISIONAL CINA DI JADE MUSIC SCHOOL JALAN SINGOSARI NO. 3 F. MEDAN - Henroy Samuel Siboro (Grenek: Jurnal Seni Musik, 2013)
The existence of this Chinese Tradisonal music instrument is know by people and seldom used at the become not sacral because the arrival of modern music that can be sepatrated from daily life that can’t depend on any else. Method used to learn this Guzheng instrument isn’t so easy, because that instrument is very hard to teach, if it learned rarely. Guzheng is Traditional music instrument from China. It is the oldest music intrument in China and it has 21 gstring. Guzheng gives a separate color for itself. All this time Guzheng is never known by people or Indonesia people specially Chinese people in Medan. Jade Music School is one of a music course that teach how to play traditional music instrument specially for Guzheng. Jade Music School tries to introduce Guzheng in Medan specially for Chinese people in Medan and international. Guzheng is starting known through a Jade Music School show. Jade Music School tries to introduce, to show, and to perpetuate Guzheng as a Chinese traditional music instrument to progress Chinese people in Medan. Guzheng music instrument in Jade Music School can be accompanied by another music instrument. Guzheng has a role to bring the melody in every show.